2023
DOI: 10.1371/journal.pone.0287641
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional study of fear of surgery in female breast cancer patients: Prevalence, severity, and sources, as well as relevant differences among patients experiencing high, moderate, and low fear of surgery

Abstract: Background Fear of surgery has been associated with more postoperative pain, disability, and a lower quality of life among patients undergoing various surgical procedures. While qualitative studies indicate breast cancer patients to be afraid of surgery, detailed quantitative analyses are lacking. The present research aimed at investigating the prevalence, severity, and sources of fear of surgery in this patient group and to compare patients reporting different degrees of such fear. Methods This cross-sectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 83 publications
(142 reference statements)
0
0
0
Order By: Relevance
“…This study revealed that some of the participants made the decision to refuse the treatment due to fear of surgery. Fear of surgery is a prevalent and relevant phenomenon among female breast cancer patients (Engel et al, 2023). Saeed et al (2021) reported that the participants in their study purposely delayed the treatment due to the fear of mastectomy and loss of femininity.…”
Section: Discussionmentioning
confidence: 99%
“…This study revealed that some of the participants made the decision to refuse the treatment due to fear of surgery. Fear of surgery is a prevalent and relevant phenomenon among female breast cancer patients (Engel et al, 2023). Saeed et al (2021) reported that the participants in their study purposely delayed the treatment due to the fear of mastectomy and loss of femininity.…”
Section: Discussionmentioning
confidence: 99%
“…A preliminary study conducted among 65 patients awaiting cardiac surgery provided promising results regarding the reliability of the scale (Cronbach's a coefficient for the full scale was 0.93, for short-term aspects of surgery was 0.91, and for long-term surgery aspects was 0.90). The SFQ questionnaire has been used in studies conducted in the Netherlands [28,29], Greece [34], Portugal [35,36], Turkey [21,23,33,[37][38][39][40][41][42][43], Croatia [44], Norway [45], Germany [31], Italy [46], Czech Republic [30], China [32], United States [47,48], Ireland [49], and Hungary [50][51][52]. Most of these publications appeared in the years 2022-2023.…”
Section: Prospective Evaluation Monitoring the Level Of Anxietymentioning
confidence: 99%